Identify the relationship between personality factors and empathy for animals. - Călin, Mariana Floricica; Sandu, Mihaela Luminița; Simioana (Lazăr), Maria Adina (Technium Social Sciences Journal, 2021)
This paper aims to outline a psychological profile of people who show empathy for animals, taking into account personality factors and attachment style. Although in recent years research on the relationship between humans and animals has grown considerably, and every day more and more research is published exploring the links between humans, animals, empathy and behavior, in Romania this topic has not been of much interest. , given the tiny number of researches in this area. Empathy is often studied because it relates to humans, but there is a growing interest in the relationship, development and its impact on animals. This interest is often driven by a curiosity in the role of empathy as an internal motivator for changing pro-environmental behavior. As with many internal affective responses, the connection is not always directly clear, but growing evidence suggests that empathy may influence the likelihood of pro-environmental behaviors. It can be said with certainty that empathy can play an important role in understanding the experiences and needs of animals, and can be considered as a potential way to preserve emotional behaviors.